Macrophages, Inflammation, and Tumor Suppressors: ARF, a New Player in the Game - Paqui G. Través; Alfonso Luque; Sonsoles Hortelano (Hindawi Limited, 2012)
The interaction between tumor progression and innate immune system has been well established in the last years. Indeed, several lines of clinical evidence indicate that immune cells such as tumor-associated macrophages (TAMs) interact with tumor cells, favoring growth, angiogenesis, and metastasis of a variety of cancers. In most tumors, TAMs show properties of an alternative polarization phenotype (M2) characterized by the expression of a series of chemokines, cytokines, and proteases that promote immunosuppression, tumor proliferation, and spreading of the cancer cells. Tumor suppressor genes have been traditionally linked to the regulation of cancer progression; however, a growing body of evidence indicates that these genes also play essential roles in the regulation of innate immunity pathways through molecular mechanisms that are still poorly understood. In this paper, we provide an overview of the immunobiology of TAMs as well as what is known about tumor suppressors in the context of immune responses. Recent advances regarding the role of the tumor suppressor ARF as a regulator of inflammation and macrophage polarization are also reviewed.